Physico Chemical Characteristics of Lakhna Devi Temple Water Tank, Lakhna, Bakewar, Etawah, U.P. with reference to Cyanobacterial Diversity - Bajpai, Omesh; Mishra, Sujata; Mohan, Narendra; Mohan, Jitendra; Gupta, Rajan K (International Journal of Environment, 2013)
Fresh water bodies in populated plains of tropical countries face various disturbances in the form of pollutant and nutrient inflow, heavy metal and elemental precipitation (wet or dry) and constant silt inflow (natural or anthropogenic). The physico-chemical characteristics are very much important for any water body. In lentic water bodies these characteristics shows very much variation because in summer they have less and in rains large amount of water. These adverse constrain effectively influence the algal assemblage and can be a good indicator of overall health of the water body. In the study different Physico-chemical characteristics and algal diversity were monthly observed for one year duration (Jun. 2008 to May 2009). Some of 31 species of Cyanobacteria recorded from the study site viz. Microcystis aerughinosa, M. flos-aquae, M. robusta, Chroococcus minor, C.minutes, Gloeocapsa magma, Aphanocapsa littoralis, Aphanothece microscopis, Coelosphaerium kuetzingianum, Merismopedia glauca, M. tenuissima, Arthrospira spriulinoides, Spirulina gigantean, S. major, Oscillatoria formosa, O. subuliformis, O. princeps, Phormidium ambiguum, P. fragile, P. lucidum, Lyngbya contorta, O. epiphytica, O.majuscule, Cylindrospermum minutissimum, Nostoc commune, N. punctiforme, Anabaena oscillarioides, A. oryzae, Calothrix gloeocola, Rivularia aquatic and Gloeotrichia pisum. DOI: http://dx.doi.org/10.3126/ije.v1i1.8525 International Journal of Environment Vol.1(1) 2013: 20-28